Stem components of hibiscus sabdariffa L. for papermaking - Risma, bt Rahman. (Universiti Malaysia Sarawak (UNIMAS), 2004)
The calyx of Hibiscus sabdarifJa L. (roselle) is commercially used as a source of raw material in the food industries. Besides their calyx, this non-woody plant is not beneficial and more often discarded after their economic harvesting period. This experiment was carried out mainly to evaluate the suitability of its stem components for papermaking and determine which stem components would produce superior handsheet properties. The stem components of roselle were collected and prepared into 20 to 30 cm length. The samples were pulped with different levels of active alkalis (l0%, 12%, 14% and 16%) and beaten with different degrees of beating revolution (0, 2500 and 5000). As a result, roselle stem component (bast and core) were determined to have superior fibres than the control sample of A. mangium and were able to produce comparable if not better properties of handsheets than A. mangium.